Role of intraoperative imprint cytology in diagnosis of cervical lymph node metastasis: Role of intraoperative imprint cytology in diagnosis of cervical lymph node metastasis - Chaowchuen, Sitthi; Kittiya Taengon; Loonprom, Komsan; Wiwatwarayos, Kulachet; Ruangsomboon, Pakpoom; Ruangsomboon (Makdee), Onlak (Thai Journal of Otolaryngology Head and Neck Surgery, 2025)
The intraoperative sentinel lymph node biopsy is a recognized method to determine the stage of head and neck cancers. This procedure assists in the diagnosis of cancer metastasis. Cytology and pathology are crucial processes for tissue diagnosis during surgery. However, due to insufficient pathologists available to interpret frozen section pathology in all hospitals. Therefore, imprint cytology presents itself as an alternative. This study aims to assess the sensitivity and specificity of intraoperative imprint cytology diagnosis compared to pathology in detecting cancer metastasis to the lymph nodes in the neck. Result: The study found that 46 patients participated in the research, with a total of 322 lymph nodes examined. The majority of patients were female, with 26 cases (56.52%) which 23-80 years old (Mean 53.93, SD 14.43). The two most common types of head and neck were thyroid cancer (22 cases, 47.83%) and oral cancer (18 cases, 39.13%). The two most common pathological types were papillary thyroid carcinoma and squamous cell carcinoma, each found in 21 cases (45.65%). Most patients were in stage 4 of cancer (22 cases, 47.83%). Most patients underwent selective neck dissection (31 cases, 67.31%) and comprehensive neck dissection (15 cases, 32.61%). The prevalence of cervical lymph node metastasis in this study was 20.5% (95%CI 16.2-25.3). The sensitivity of imprint cytology compared to pathology was 87.9% (95%CI 77.5-94.6%), and its specificity was 94.9% (95%CI 91.5-97.3%). The positive predictive value (PPV) was 81.7% (95%CI 70.7-89.9%), and the negative predictive value (NPV) was 96.8% (95%CI 93.8-98.6%). These results indicate that imprint cytology has a high sensitivity of 87.9% and a specificity of 94.9%, resulting in a PPV of 81.7% and an NPV of 96.8%. This study’s findings suggest that imprint cytology can be a reliable method for detecting cancer metastasis to the lymph nodes in the neck. Particularly, a negative result from imprint cytology is highly reliable, which can help avoid extensive neck dissection surgeries, thereby reducing the complications associated with neck lymph node removal.